Design and optimization of microstrip filtering antenna with modified shaped slots and SIR filter to improve the impedance bandwidth - Hana Abdel-Jabbar; Ahmed Sabri Kadhim; Ameer L. saleh; Yasir I. A. Al-Yasir; Naser Ojaroudi Parchin; Raed A. Abd-Alhameed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents a new compact microstrip filtering antenna with modified shaped slots to improve the impedance bandwidth. The proposed microstrip filtering antenna consists of three parts; the monopole radiating patch antenna, the SIR filter, and the feeding microstrip line. The design structure is achieved on one sided glass epoxy FR-4 substrate with dielectric constant ε_r = 4.4 and thickness of h = 1.6 mm. The design procedures of the proposed filtering antenna starts from the second order Chebyshev low pass filter prototype. The simulation results throughout this article are done by a computer simulation technology (CST) software. The simulated results have been achieved show good performance of S11-parameter and broad side antenna gain on +z-direction. This design has two transmission zeros at 5.4 GHz and 7.7 GHz, and bandwidth (B.W) of about 1.66 GHz so; it is suitable for high speed data communication. This design has good skirt selectivity.